Implementasi Penggunaan E-Office di Bappedalitbang Provinsi Riau: Analisis Model Charles O Jones - Tsakila Harefa, Qaulan; Museliza, Virna; Nurani, Ratna (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This study aims to analyze the implementation of e-Office usage at the Regional Development Planning, Research, and Development Agency (Bappedalitbang) of Riau Province and to identify its supporting and inhibiting factors using Charles O. Jones' implementation theory, which includes organization, interpretation, and application. The research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that although the implementation of e-Office has been in place for some time at Bappedalitbang Riau Province, it has not been carried out consistently. This inconsistency is mainly due to uneven training provided by the agency, resulting in a lack of employee knowledge about the use of the e-Office system, as well as the absence of evaluation efforts by Bappedalitbang regarding the system. However, there are supporting factors, such as the availability of hardware and upgraded internet networks, which were intentionally improved to optimize the use of the e-Office system at Bappedalitbang. The specific contribution to policy implementation theory lies in emphasizing the importance of key factors in the implementation process and how these factors play a role in the context of digital policy implementation in government institutions. Practically, the findings of this study can serve as a reference for Bappedalitbang in implementing the e-Office system, particularly in addressing the current inhibiting factors. Theoretically, these findings reinforce Charles O. Jones’ policy model by highlighting the complex interactions between organization, interpretation, and application within the context of digital policy.